In vitro Antibiotic and Antifungal Sensitivity Pattern of Bacterial and Fungal Isolates from Otitis Externa in Dogs - Barua, Arpana; Barman, Ditul; Baishya, Bhaben Chandra; Phukan, Arabinda; Dutta, Jyoti B.; Hazarika, Girin (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The objective of the present study was to evaluate the in-vitro antibiotic and antifungal sensitivity test of the 55 bacterial and 20 fungal isolates from otitis dogs. The antibiotic sensitivity test for coagulase-positive Staphylococcus species revealed the highest sensitivity to ceftriaxone & tazobactam (100.00%), Coagulase-negative Staphylococcus species to Ceftriaxone & tazobactam and Enrofloxacin (100.00%), Streptococcus species to Enrofloxacin & Ofloxacin (88.88%); however, Gram-negative organisms like Escherichia coli and Pseudomonas species revealed highest (100.00%) sensitivity to enrofloxacin. Malassezia pachydermatis and Candida species revealed 100% sensitivity to Ketoconazole, Clotrimazole, and Itraconazole in AFST.